Building a Cyber Foundation: A Strategic Policy for Improving the Quality of Digital Learning at UIN Siber Syekh Nurjati Cirebon - Deding Sudarso (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This policy paper examines the urgency and strategies for improving the quality of digital learning at UIN Siber Syekh Nurjati Cirebon. In line with the global educational transformation, UIN Siber has great potential to become a leading technology-based institution. However, this success depends heavily on a solid cyber foundation, encompassing infrastructure, human resources, and well-planned policies. This paper analyzes the current state of digital learning, identifying key challenges such as access gaps, limited faculty capacity, and content standardization. The approach used is a comprehensive literature review and qualitative policy analysis, which formulates a strategic framework to address these challenges. The analysis results indicate the need for an integrated policy encompassing three main pillars: strengthening information technology infrastructure, developing human resource (HR) capacity through intensive training, and developing relevant and interactive digital curricula and content. Furthermore, this article proposes a continuous monitoring and evaluation system to ensure effective implementation. By implementing this strategy, it is hoped that UIN Siber Syekh Nurjati Cirebon will be able to create an adaptive, innovative, and globally competitive learning environment, making digital learning not merely an alternative but a core part of the vision of future education.